HUBUNGAN MASA KERJA TERHADAP GANGGUAN FUNGSI PARU PADA PETUGAS PENYAPU JALAN DI PROTOKOL 3, 4 DAN 6 KOTA SEMARANG - Riska Wulandari; Onny Setiani; Niki Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Transportation activities contributed significantly to air pollution, one of which was a parameter of dust. Workers were exposed to dust in the work environment can lead to accumulation of dust particles in the lungs. Officers street sweeper was a high-risk workers exposed to dust while working, especially in Protocol 3, 4 and 6 of Semarang where approaching the location of the measurement sample ambient air quality that exceeds the threshold value. The purpose of this study was the relationship working duration against lung function disorder on a street sweeper in Protocol 3, 4 and 6 Semarang. This type of research was observational research with cross sectional approach. The population was Street Sweeper in Protocol 3, 4 and 6 of Semarang, amounting to 61 people with a sample of 38 people with purposive sampling method. Results of univariate analysis found an average of forced vital capacity (FVC%) of 84.515%, the average forced expiratory volume in the first second (FEV1%) of 82.875% and an average of 90.230%. Bivariate analysis of the relationship between the working duration and lung function disorder used Chi Square test show p-value of 0,034 (PR = 4.371; 95% CI = 1.074 to 17.79). The conclusion was significant association between the work duration and lung function disorder on street sweeper in a street sweeper in Protocol 3, 4 and 6 Semarang. The Suggestions in this study is expected to be a consideration for the relevant agencies in general and the Cleanliness and Landscaping Departement can be used as a reference for the implementation of programs related to the effects of exposure to dust on the street sweeper.